DEVELOPMENT OF URBAN FARMING CARAMEL MELON ON NARROW LAND THROUGH DRIP IRRIGATION TECHNOLOGY FOR THE YOUNGER GENERATION - Anuar Januar Rahman; Ivonne Ayesha (Journal of Community Service, 2026)
The utilization of limited land provides an alternative approach to promoting productive agricultural activities among young people. Limited land availability requires the application of cultivation technologies that can optimize the use of space and resources, one of which is the cultivation of Caramel Melon using a drip irrigation system. This community service program aimed to implement drip irrigation technology for Caramel Melon cultivation on limited land while providing young people with practical experience in utilizing available land for agricultural activities. The program was conducted from July to August 2025 in Cipadung Village, Bandung City, involving 21 participants. A participatory approach was employed through hands-on activities, including land clearing, construction of a shade structure, preparation and incubation of the growing media, seedling preparation, filling polybags, transplanting and replacing seedlings, construction and installation of the drip irrigation system, plant maintenance, trellising, and flower and fruitlet selection. The success indicator was the successful implementation of drip irrigation technology in Caramel Melon cultivation on land that had previously been underutilized. The irrigation system utilized a water reservoir and drip pipes to deliver water more directly to the plant root zones. Participants were actively involved in each stage of the activity, providing them with practical experience in applying cultivation technology on limited land. The activity demonstrates that drip irrigation can serve as an alternative technology for developing agriculture on limited land while creating opportunities for young people to utilize available space for productive agricultural activities.